Sex differences in clinical phenotype and transitions of care among individuals dying of COVID-19 in Italy - Valeria Raparelli; Luigi Palmieri; Marco Canevelli; Flavia Pricci; Brigid Unim; Cinzia Lo Noce; Emanuele R. Villani; Paula A. Rochon; Louise Pilote; Nicola Vanacore; Graziano Onder; Italian National Institute of Health COVID-19 Mortality Group (Biology of Sex Differences, 2020)
Abstract Background Among the unknowns posed by the coronavirus disease 2019 (COVID-19) outbreak, the role of biological sex to explain disease susceptibility and progression is still a matter of debate, with limited sex-disaggregated data available. Methods A retrospective analysis was performed to assess if sex differences exist in the clinical manifestations and transitions of care among hospitalized individuals dying with laboratory-confirmed SARS-CoV-2 infection in Italy (February 27–June 11, 2020). Clinical characteristics and the times from symptoms’ onset to admission, nasopharyngeal swab, and death were compared between sexes. Adjusted multivariate analysis was performed to identify the clinical features associated with male sex. Results Of the 32,938 COVID-19-related deaths that occurred in Italy, 3517 hospitalized and deceased individuals with COVID-19 (mean 78 ± 12 years, 33% women) were analyzed. At admission, men had a higher prevalence of ischemic heart disease (adj-OR = 1.76, 95% CI 1.39–2.23), chronic obstructive pulmonary disease (adj-OR = 1.7, 95% CI 1.29–2.27), and chronic kidney disease (adj-OR = 1.48, 95% CI 1.13–1.96), while women were older and more likely to have dementia (adj-OR = 0.73, 95% CI 0.55–0.95) and autoimmune diseases (adj-OR = 0.40, 95% CI 0.25–0.63), yet both sexes had a high level of multimorbidity. The times from symptoms’ onset to admission and nasopharyngeal swab were slightly longer in men despite a typical acute respiratory illness with more frequent fever at the onset. Men received more often experimental therapy (adj-OR = 2.89, 95% CI 1.45–5.74) and experienced more likely acute kidney injury (adj-OR = 1.47, 95% CI 1.13–1.90). Conclusions Men and women dying with COVID-19 had different clinical manifestations and transitions of care. Identifying sex-specific features in individuals with COVID-19 and fatal outcome might inform preventive strategies.